Increased Glutamate Dehydrogenase Activity in Alcohol Dependent Persons: A Novel Old Marker - Matej Kravos (Recent Developments in Chemistry and Biochemistry Research Vol. 10, 2025)
Alcoholism has a pronounced effect on people’s mental and physical health; in addition, it greatly influences family life as well as social and professional environments. It can be indirectly ascertained by means of some biochemical markers in serum, such as carbohydrate-deficient transferrin (CDT), gamma-glutamyl transferase (GGT), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and mean corpuscular volume (MCV). Combinations of alcohol markers increase sensitivity and diminish specificity. The aims of this study were as follows: to estimate and determine the role of GLDH as a marker of alcoholism, maintenance of abstinence and recurrence of alcohol consumption, and to define its specifics, sensitivity and clinical applicability. Also in the combinations with other markers after new findings about it were discovered. The list of alcohol dependence markers in blood was assessed in 238 alcohol-dependents admitted to the hospital and 111 healthy individuals. A blood sample was taken from every alcohol-dependent three times: on admission, after 24 hours and after seven days. Alcohol-dependents were ascertained to have higher GLDH serum activities (mean activities in men 351.53 nkat/L, women 296.08 nkat/L), the higher, the less elapsed time there was after the latest alcohol intake. In comparison with other markers, the decrease in GLDH activity is the fastest within the first 24 hours, whereas with AST and GLDH after 7 days. The kinetics of GLDH and AST is more applicable than GGT kinetics after a week’s cessation of drinking, but GLDH kinetics are the most reliable. As no marker is known to be sufficiently specific and sensitive to diagnose chronic excessive alcohol intake, combinations of alcohol markers increase sensitivity and diminish specificity. With almost 90% specificity, GLDH was found to be the most specific laboratory marker, but a combination of GLDH and AST reached the highest specificity with 82%. The sensitivity of the combination of MCV and GLDH kinetics after one week of abstinence was indicative of 97.2%. Designed were some recommended combinations, e.g. the combination which determines MCV and GLDH kinetics in serum (a fall in the activity after 7 days) provides a 97.22% diagnostic sensitivity to alcohol addiction. GLDH is an equally accurate marker of alcoholism over GGT or CDT if a significantly faster decrease in its activity since the last alcohol consumption in alcohol dependents is taken into consideration and is not overlooked. Therefore, watching that increased GLDH activity in sera of alcohol-dependents and the return of serum GLDH to normal activity is an effective yet overlooked aid in diagnostic cessation of drinking as a specific marker of alcohol addiction.